Poverty in Pakistan: trends and issues - Ashfaq, M.; Jehangir, Waqar A.; Hussain, Intizar; Mudasser, Mudasser (2004)
The phenomenon of poverty is receiving the increasing attention of policy makers and institutions with an attempt to improve the living standards of the third world countries. Pakistan is no exemption to that. As the majority of third world population is concentrated in rural areas and dependent on agriculture sector for income, it becomes of special interest to dig into the root causes of poverty in these areas. A number of studies have shown that poverty is concentrated in the rural areas of Pakistan. However, a wide variation in estimates of poverty was experienced owing to various approaches and different poverty lines used by the researchers in estimating the incidence, depth, and severity of poverty. Recently, the Government of Pakistan addressed this issue by circulating the official poverty line. Poverty being a complex phenomenon, its determinants vary from time to time and across different areas. However, most of the studies indicate that poverty in Pakistan is concentrated in rural areas of Pakistan. Applying dollar a day poverty line shows that the poverty in Pakistan is higher as compared with many other Asian countries.